Student Engagement Reviewed Based on Gender and Academic Year - Muhammad Fadhli; Zesi Aprillia; Ridzqie Dibyantari (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to determine differences in student engagement by gender and academic year. A quantitative approach with a comparative research design was chosen to answer the research objectives. A total of 379 active students participated in this study, selected using accidental sampling. Data were obtained using a student engagement scale and analysed using ANOVA. The results of the study found that: 1) There was no difference in student engagement based on gender (significance value = 0.400). 2) There was a significant difference in student engagement based on academic year (significance value = 0.001); further analysis showed that first-year students had the highest mean score compared to students in higher years. From these results, it can be concluded that there was no difference in student engagement by gender, whereas by academic year, there was a significant difference. This study provides new insights into the factors of gender and academic year that can impact student engagement. It is hoped that future studies can conduct in-depth analysis using confirmatory factor analysis (CFA) on related variables and involve a more diverse range of subjects.